Peran Diplomasi Maritim dalam Keberhasilan Patroli Terkoordinasi Indonesia-Malaysia-Singapura untuk Menekan Angka Pembajakan dan Perompakan Laut di Selat Malaka - Lintang Suproboningrum (Universitas Airlangga, 2018)
This research is study of maritime security cooperatioon among Indonesia, Malaysia and Singapore in safeguarding the Malacca Strait from threats to maritime security in the area. This research uses Maritime Diplomacy concept as tool to measure the sucess of coordinated patrol in the Malacca Strait. The focus of this research is to analyze the dynamic of international security in the Southeast Asia. Malacca Strait is chosen because it is one of the most important waterways in the world. One of the biggest issue in the Malacca Strait is the threat of piracy and armed robbery. The three states which is located around Malacca Strait respond to this threats by creating a new initiative for tackling maritime security called Coordinated Patrol in 2004. This research conclude that the fulfillment of responsibility for security in the Malacca Strait can suppress the threats of piracy and armed robbery. The Coordinated Patrol held by the three states in Malacca strait also proves that Maritime Diplomacy is a key to the exercise of success in responding to the problems of shared area. Through Maritime Diplomacy, the three states in the Malacca Strait successfully overcome the threats to the shared area among the three states.